Biallelic loss of function variants in PPP1R21 cause a neurodevelopmental syndrome with impaired endocytic function. Issue 3 (25th December 2018) - Rehman, Atteeq U.; Najafi, Maryam; Kambouris, Marios; Al‐Gazali, Lihadh; Makrythanasis, Periklis; Rad, Abolfazl; Maroofian, Reza; Rajab, Anna; Stark, Zornitza; Hunter, Jill V.; Bakey, Zeineb; Tokita, Mari J.; et al.
Abstract: Next‐generation sequencing (NGS) has been instrumental in solving the genetic basis of rare inherited diseases, especially neurodevelopmental syndromes. However, functional workup is essential for precise phenotype definition and to understand the underlying disease mechanisms. Using whole exome (WES) and whole genome sequencing (WGS) in four independent families with hypotonia, neurodevelopmental delay, facial dysmorphism, loss of white matter, and thinning of the corpus callosum, we identified four previously unreported homozygous truncating PPP1R21 alleles: c.347delT p.(Ile116Lysfs*25), c.2170_2171insGGTA p.(Ile724Argfs*8), c.1607dupT p.(Leu536Phefs*7), c.2063delA p.(Lys688Serfs*26) and found that PPP1R21 was absent in fibroblasts of an affected individual, supporting the allele's loss of function effect. PPP1R21 function had not been studied except that a large scale affinity proteomics approach suggested an interaction with PIBF1 defective in Joubert syndrome. Our co‐immunoprecipitation studies did not confirm this but in contrast defined the localization of PPP1R21 to the early endosome. Consistent with the subcellular expression pattern and the clinical phenotype exhibiting features of storage diseases, we found patient fibroblasts exhibited a delay in clearance of transferrin‐488 while uptake was normal. In summary, we delineate a novel neurodevelopmental syndrome caused by biallelic PPP1R21 loss of function variants, and suggest a role of PPP1R21 within the endosomal sorting process or endosome maturation pathway. Abstract : We describe PPP1R21 loss of function in 4 independent families with syndromal neurodevelopmental delay by exome and genome sequencing. Immunoflorescence analysis reveals wildtype PPP1R21 localises to the early endosome and PPP1R21 loss of function in patient fibroblasts results in disturbances of the endosomal sorting process or endosome maturation pathway.